Does participation in Downhill mountain biking affect measures of executive function? - Hurst, H. T.; Hancock, S.; Hardwicke, J.; Anderson, E. (Journal of Science and Cycling, 2020)
This study assessed the influence of downhill mountain biking on acute measures of executive function. Twenty-three participants took part in the study and were assigned to either, FIELD (N=7, mean age 27 ± 9 yrs), LAB (N=8, mean age 36 ± 9 yrs) or CONTROL (N=8, mean age 41 ± 9 yrs) groups. Participants performed the Stroop colour-word test via a tablet pc app (EncephalApp). Additionally, the Trail Making Test A (TMT-A) and B (TMT-B) were completed. Significant main effects were found for OffTime (F2,12 = 13.04; p = .001; etap2 = .69), OnTime (F2,12 = 4.31; p = .04; etap2 = .42) and OnTrials (F2,12 = 10.74; p = .002; etap2 = .64), with the results showing a decrement in Stroop test performance following Trial1 and Trial4 compared to BL for the FIELD group. A significant main effect was found for TMT-A (F2,12 = 7.50; p = .008; etap2 = .56), with performance improving following Trial4 compared to BL for the FIELD group. LAB and CONTROL groups significantly improved on the TMT-B from BL to Trial1 and Trial4 (F2,14 = 4.31; p = .04; etap2 = .38 and F2,14 = 13.70; p = .001; etap2 = .66, respectively). Results suggest participation in downhill mountain biking in this cohort significantly impaired executive function when compared to repeated sprint activity within a laboratory. This is indicative of repeated head accelerations caused by riding over rough terrain.